Analisis Kinerja Keuangan Sebelum dan Saat Pandemi Covid-19 pada Pemerintah Daerah Provinsi di Indonesia Tahun 2018-2021 - Riska Venni; Afridian Wirahadi Ahmad; Ulfi Maryati (Universitas Batanghari Jambi, 2023)
This study aims to determine differences in the financial performance of provincial and local governments in Indonesia regarding financial independence, capital expenditure, tax ratio, short-term solvency and financial flexibility in provincial, local governments in Indonesia in 2018-2021. This research uses secondary data from LHP LKPD 34 provinces in Indonesia in 2018-2021. The sampling technique uses a saturation sampling technique. Data analysis methods using SPSS 26 and hypothesis testing using paired sample t-test and Wilcoxon signed rank test. The results of the study prove that the ratio of financial independence, tax ratio, and short-term solvency did not experience a significant difference before and during the Covid-19 pandemic, while the ratio of capital expenditure and financial flexibility experienced differences before and during the Covid-19 pandemic, which were influenced by policies. Social restrictions, policy refocusing and reallocation of the 2020 APBD